IFI27/ISG12 Downregulates Estrogen Receptor α Transactivation by Facilitating Its Interaction With CRM1/XPO1 in Breast Cancer Cells - Cervantes-Badillo, Mayte Guadalupe; Paredes-Villa, Alejandro; Gómez-Romero, Vania; Cervantes-Roldán, Rafael; Arias-Romero, Luis E.; Villamar-Cruz, Olga; González-Montiel, Miroslava; Barrios-García, Tonatiuh; Cabrera-Quintero, Alberto J.; Rodríguez-Gómez, Gabriel; Cancino-Villeda, Laura; Zentella-Dehesa, Alejandro; et al. (Frontiers in Endocrinology, 2020)
The estrogen receptor alpha (ER alpha) is a ligand-activated transcription factor whose activity is modulated by its interaction with multiple protein complexes. In this work, we have identified the protein interferon alpha inducible protein 27 (IFI27/ISG12) as a novel ER alpha-associated protein. IFI27/ISG12 transcription is regulated by interferon and estradiol and its overexpression is associated to reduced overall survival in ER+ breast cancer patients but its function in mammary gland tissue remains elusive. In this study we showed that overexpression of IFI27/ISG12 in breast cancer cells attenuates ER alpha transactivation activity and the expression of ER alpha-dependent genes. Our results demonstrated that IFI27/ISG12 overexpression in MCF-7 cells reduced their proliferation rate in 2-D and 3-D cell culture assays and impaired their ability to migrate in a wound-healing assay. We show that IFI27/ISG12 downregulation of ER alha transactivation activity is mediated by its ability to facilitate the interaction between ER alpha and CRM1/XPO1 that mediates the nuclear export of large macromolecules to the cytoplasm. IFI27/ISG12 over-expression was shown to impair the estradiol-dependent proliferation and tamoxifen-induced apoptosis in breast cancer cells. We hypothesize that IFI/27/ISG12 over-expression in breast cancer tumors may participate in the development of tamoxifen-resistant cells. Our results suggest that IFI27/ISG12 may be an important factor in regulating ER alpha activity in breast cancer cells by modifying its nuclear versus cytoplasmic protein levels. We propose that IFI27/ISG12 may be a potential target of future strategies to control the growth and proliferation of ER-positive breast cancer tumors.